Soeharto and the Politics of Democratization: Managing Openness in Indonesia’s New Order - Agil Kurniadi; Roby Rakhmadi (Jurnal Terekam Jejak, 2026)
This study examines the democratization process during the New Order government. The study attempts to understand and trace President Soeharto's response to the current of democratization in Indonesia, influenced by the global political constellation. The analysis reveals that President Soeharto had his own unique approach to responding to this trend. He did not simply accept the liberal Western democratic ideals, but instead sought to adapt them to suit his own Indonesian context. This study utilizes historical methods, including heuristics, verification, interpretation, and historiography. The conclusion is that the democratic space developed by Soeharto was a "half-hearted" democracy. This study demonstrates that the New Order government was not overly rigid, and the political dynamics it fostered resulted in political compromises.